IMPLEMENTATION OF THE DOUBLE LOOP PROBLEM SOLVING (DLPS) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN DRUGS IN CLASS X MM 2 SMK NEGERI 1 PUNGGING - Cahyoko Tri Alianto (Jurnal Scientia, 2022)
This study aims to determine student learning outcomes on drug material through the application of the Double Loop Problem Solving (DLPS) learning model at SMK Negeri 1 Pungging Mojokerto class X MM 2 semester 1 of the 2022/2023 academic year. This research is classroom action research (CAR) which was carried out at SMK Negeri 1 Pungging Mojokerto class X MM 2 semester 1 of the 2022/2023 academic year, from August to September 2022. The research was carried out through 2 cycles with each cycle consisting of planning, implementation, observation (observation), and reflection. Based on the results of research and discussion, it can be concluded that the application of the double loop problem solving learning model can improve student learning outcomes. This can be seen from the increase in mastery learning outcomes from the first cycle to 86.11% then increased in the second cycle to 91.66%. In addition, the application of the double loop problem solving learning model in class X MM 2 SMK Negeri 1 Pungging semester 1 for the 2022/2023 academic year in Physical Education and Health subjects with the subject matter of drugs can increase student activity, implementation of lesson plans and student scientific behavior. And the average student learning outcomes also increased rapidly from the first cycle of 81.12 increased to 86 in the second cycle.